Identifying patterns, inequalities, and opportunities in adult social care through national linked data insights - Scourfield, Jonathan; Lugg-Widger, Fiona; Akbari, Ashley; Cannings-John, Rebecca; Curds, Matt; Fernandez, Jose-Luis; Meindl, Mel; Trigg, Lisa; Warner, Nell; Willis, Paul; Evans, Miranda; Cumming, Oliver; et al. (International Journal of Population Data Science, 2025)
Objectives To describe adult care and support patterns across Wales, examining variations by socio-demographic characteristics, impairments and health conditions, and deprivation. This study aims to identify disparities in care provision across individuals and areas to inform equitable service delivery and improve outcomes for adults receiving local authority (LA) care and support. Methods The Adults Receiving Care and Support (ARCS) census became a mandatory data return to the Welsh Government in April 2023. The CARE Lab is a data partnership between ADR Wales, Welsh Government, Swansea University, London School of Economics, Disability Wales, Social Care Wales and Cardiff University, integrating data from adult social care, children’s social care, health care and the 2021 Census. This initiative advances the understanding of adults receiving LA care and support, enabling detailed analysis of socio-demographic factors and inequalities. The findings will support service planning, policy evaluation, and strategies to reduce disparities in care provision across Wales. Results We will present highlights related to the initial 2023/24 ARCS standalone data collection, offering a detailed profile of adults with care and support plans. Analysis includes demographic breakdowns, intersections of socio-demographic factors, and variations in care durations. Additionally, it examines whether individuals had active care or support on the census date. Insights reveal patterns of care provision and identify areas of potential inequality or unmet need. These findings serve as a baseline for future comparisons and analyses, supporting targeted interventions to address disparities in adult social care services, and enable planning for future research for the CARE Lab and other researchers interested in the ARCS data, and suggestions towards the future primary data collection of the ARCS data. Conclusion This study will be the first UK study to explore adult social care at a national level using individual-level population-scale linked data sources. Findings will inform future data collection improvements, provide actionable insights for policy and practice, and offer an early snapshot of the population receiving LA care and support.